Analisis Penerapan Laporan Keuangan Berdasarkan Standar Akuntansi Keuangan Entitas Tanpa Akuntabilitas Publik (Sak Etap) Pada Pondok Pesantren ****** - Patimah, Siti (JYRS: Journal of Youth Research and Studies, 2021)
In the process of preparing financial statements, there are components used, consisting of a general cash book, income, expenses, and income statement. donations from guardians of students or other people, and assistance from the regional/central government. The sources of income for Islamic boarding schools are boarding fees, convenience store fees, canteen fees, TKQ/TPQ tuition fees, and Madrasah Diniyah tuition fees. In this study, the researchers used the type of field research. The type of research in this research is descriptive qualitative. Descriptive research is research that is able to do business and can explain a symptom, event, event, which is happening. Descriptive research focuses its attention on actual problems as happens when conducting direct research. With this qualitative descriptive research, the researcher tries to explain the events or events where the central point is of concern without giving special treatment to the event. In preparing financial reports at the ****** Islamic Boarding School, making financial reports such as cash books, income and expenditure reports, Islamic boarding schools make simple financial reports, namely recording cash receipts and expenses where transactions are carried out at the pesantren. To record the financial statements of PONPES, it is carried out by the financial manager which will be signed by the leader, treasurer or secretary. This report is prepared as accountability for the activities that have been carried out and then submitted to the leadership of PONPES.